Impact of consumption values on cashless society: influence of perceived costs - Tanha, Moutusi; Bhuiyan, Nayem Mahmud; Mukhopadhyay, Sudipta; Mannan, Sayed Sajib; Nath , Subroto Deb; Islam , Md. Nasirul; Muhammad Al Amin (Annals of Management and Organization Research, 2025)
Purpose: This study aims to investigate the influence of consumption values (functional, social, emotional, epistemic, and conditional) on adopting a cashless society while examining the moderating effect of perceived cost and the mediating effect of cashless readiness. Research Methodology: A quantitative research approach was employed, utilizing a convenience sampling method to collect data from 200 respondents through a survey. Statistical analysis techniques such as structural equation modeling (SEM) were likely used to analyze the data and test the hypothesized relationships. Results: The study reveals that functional, epistemic, and conditional values significantly impact cashless readiness, which in turn affects the adoption of a cashless society. Perceived cost is identified as a significant moderator between cashless readiness and the adoption of a cashless society. Additionally, the findings indicate that cashless readiness partially mediates the relationship between functional, epistemic, and conditional values and the adoption of a cashless society. Limitations: A potential limitation could be the use of a convenience sampling method, which may affect the generalizability of the findings to a larger population. Contributions: The findings of this study could be valuable for mobile financial service providers, banking institutions, and governmental organizations in developing strategies to increase the adoption of digital payment systems. It contributes to the existing literature on consumer behavior and technology adoption, specifically in the context of cashless societies and mobile financial services.